How to Understand “Herd Immunity” in COVID-19 Pandemic - Xia, Yuanqing; Zhong, Lumin; Tan, Jingcong; Zhang, Zhiruo; Lyu, Jiajun; Chen, Yiting; Zhao, Anda; Huang, Lili; Long, Zichong; Liu, Ning-Ning; Wang, Hui; Li, Shenghui (Frontiers in Cell and Developmental Biology, 2020)
The COVID-19 pandemic has been a global threat. Through rapid and effective surveillance and control, China's response has achieved a stage victory. By contrast, the epidemic of COVID-19 in other countries out of China is bursting. Different countries are adopting varied response strategy in terms of their public health system to prevent the spread. Herd immunity has been a hot word most recently. Can it be a possible strategy to combat COVID-19? To fully interpret the knowledge regarding the term upon the background of COVID-19-related health crisis, we aim to systematically review the definition, describe the effective measures of acquiring herd immunity, and discuss its feasibility in COVID-19 prevention. Findings from this review would promote and strengthen the international cooperation and joint efforts when confronting with COVID-19.